2014
DOI: 10.1161/atvbaha.113.302991
|View full text |Cite
|
Sign up to set email alerts
|

Defective Angiogenesis Delays Thrombus Resolution

Abstract: Objective Restoration of patency is a natural target of vascular remodeling following venous thrombosis that involves vascular endothelial cells and smooth muscle cells as well as leukocytes. Acute pulmonary emboli usually resolve within six months. However, in some instances, thrombi transform into fibrous vascular obstructions, resulting in occlusion of the deep veins, or in chronic thromboembolic pulmonary hypertension (CTEPH). We proposed that dysregulated thrombus angiogenesis may contribute to thrombus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 43 publications
2
45
1
1
Order By: Relevance
“…70 Recently, the sequence of events that promote deep vein thrombosis was analyzed with the use of variations of the murine vena cava ligation model. 3 In the same model, genetic deletion of platelet endothelial cell adhesion molecule 1 4 illustrated the crucial roles of leukocyte migration and angiogenesis 71 in resolution of deep vein thrombosis and resolution of thrombus in CTEPH. Despite all of this evidence, one must bear in mind the limitations of studying thrombosis and thrombus resolution in animals or in in vitro models.…”
Section: Major-vessel Diseasementioning
confidence: 98%
“…70 Recently, the sequence of events that promote deep vein thrombosis was analyzed with the use of variations of the murine vena cava ligation model. 3 In the same model, genetic deletion of platelet endothelial cell adhesion molecule 1 4 illustrated the crucial roles of leukocyte migration and angiogenesis 71 in resolution of deep vein thrombosis and resolution of thrombus in CTEPH. Despite all of this evidence, one must bear in mind the limitations of studying thrombosis and thrombus resolution in animals or in in vitro models.…”
Section: Major-vessel Diseasementioning
confidence: 98%
“…In an animal model, neutropenia was associated with larger thrombi in the second and seventh day and was correlated with higher degrees of fibrosis in the thrombus and significantly lower serum levels of plasminogen activators such as urokinase and MMP-9. Early collagenolysis seems to take place in the first 7 days, as suggested by a high rigidity in the vein wall and persists up to 14 days, being accompanied by high activity of MMP-2 and MMP-9 [35].…”
Section: The Role Of Inflammatory Markers In Thrombus Resolutionmentioning
confidence: 99%
“…In a comparative study between low weight heparins and oral P selectin inhibitors administered 2 days after the thrombosis, it was revealed that P selectin inhibitors significantly reduce the injury of the vein wall, independently of the size of thrombus [34,35].…”
Section: The Role Of Inflammatory Markers In Thrombus Resolutionmentioning
confidence: 99%
“…A bundle of converging evidence further supports the hypothesis that IP-10 and IFN-c signalling pathways are potential key players in the pathogenesis of CTEPH ( fig. 1a) and not simply innocent bystanders: 1) medical conditions with an inflammatory component, including staphylococcal infection, splenectomy, inflammatory bowel disease and osteomyelitis, are risk factors for CTEPH [22], and are associated with IP-10 secretion and/or elevated circulating IP-10 [23][24][25]; 2) IFN-c signalling could determine the relative pathogenicity of Staphylococcus aureus strains [26]; 3) venous thrombus resolution is misguided in the presence of S. aureus infection [27]; 4) IP-10 is an inhibitor of angiogenesis; and 5) defective angiogenesis delaying thrombus resolution is potentially involved in CTEPH [28], and could be promoted by splenectomy [29]. In our hands, CRP also seemed to contribute to the disease process by activating the nuclear factor (NF)-kB pathway, thereby inducing endothelial cell dysfunction in CTEPH ( fig.…”
mentioning
confidence: 99%
“…Prospective long-term follow-up studies gathering large numbers of acute pulmonary embolism patients, and combining clinical, biological and environmental parameters, are necessary to validate these pathogenic hypotheses. Similarly, development of accurate and relevant animal models clearly mimicking CTEPH pathobiology is needed, in addition to the recently developed models of abnormal venous thrombus resolution [28,29] or of large vessel mechanical obstruction [34,35].…”
mentioning
confidence: 99%